How to read the prophets: being the prophecies arranged chronologically in their historical setting with explanations - Blake, Buchanan (T. & T. Clark, 1892)
v.1. The pre-exilian minor prophets (with Joel) -- v.2. How to read Isaiah, being the prophecies of Isaiah (Ch. I.-XXXIX.) -- v.3. Jerimiah -- v.4. Ezekiel -- v.5. Isaiah (XL.-LXVI.) and the post-exilian prophets.